The effect of some insecticides, natural compounds and tomato cv. Venezia with Mi gene on the nematode Meloidogyne ethiopica (Nematoda) reproduction - Polona STRAJNAR; Saša ŠIRCA (Acta Agriculturae Slovenica)
Root-knot nematode (RKN) Meloidogyne ethiopica is quite unknown tropical plant parasitic species found in Slovenia and Europe in 2003 for the first time. The species is able to parasitize several economically important agricultural crops and therefore is very difficult to control. In our research, several approaches which can be used for M. ethiopica control were tested in pot experiment. The effects of some insecticides which are often used in the production in greenhouses, natural compounds as aqueous extract of Tagetes erecta, and the commercial natural product Azadirachtin (NeemAzal-T/S) extracted from the seeds of Indian Neem tree (Azadirachta indica) on the M. ethiopica reproduction were assessed. Test plants treatments with natural compounds reduced nematode multiplication by nearly 3 – 6 times compared to control while foliar application of Thiacloprid as well as Imidacloprid had no effect on nematode reproduction. The treatment with Volaton G granulates (Phoxim) for ground application resulted in no nematode multiplication. Additionally, M. ethiopica reproduction ability on the tomato cultivar “Venezia” which have a Mi gene for resistance to M. incognita was tested.